STRATEGY FOR STRENGTHENING CHARACTER EDUCATION THROUGH THE VALUE OF COMMUNITY SOCIAL WISDOM - Melly Agustina Permatasari; Eko Handoyo (Universitas Lambung Mangkurat, 2021)
Character is a way of thinking and behaving that characterizes each individual. Character education is a program that educates people to become moral or noble. Through character education, it is hoped that everyone will be able to implement character values and noble character in social life. The research objective is to formulate a strategy for strengthening character education through the value of social wisdom in the city of Banjarmasin. This research is descriptive analytical, namely a description of strengthening character education through the value of social wisdom in the city of Banjarmasin. The data used is secondary data, namely data obtained through library materials. All data collected were analyzed qualitatively. The results of the study show that the community has social wisdom values such as the life philosophy of the Banjar ethnic group. The value of social wisdom is used as the basis for strengthening character education which is implemented in the family environment, school environment, and community environment so that the role of local wisdom for strengthening character education will take root in the people of Banjarmasin City.